2018
DOI: 10.3389/fpls.2018.00592
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ABA Receptor VlPYL1 That Regulates Anthocyanin Accumulation in Grape Berry Skin

Abstract: ABA plays a crucial role in controlling several ripening-associated processes in grape berries. The soluble proteins named as PYR (pyrabactin resistant)/PYL (PYR-like)/RCAR (regulatory component of ABA receptor) family have been characterized as ABA receptors. Here, the function of a grape PYL1 encoding gene involved in the response to ABA was verified through heterologous expression. The expression level of VlPYL1 was highest in grape leaf and fruit tissues of the cultivar Kyoho, and the expression of VlPYL1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…Changes of polyphenol contents and gene expressions of vital enzymes involved in polyphenol biosynthesis under ABA and MLT treatments were presented in Figure 5. ABA has been widely recognized as a promotor to polyphenolic biosynthesis, and the increase in the expression of ABA receptor VIPYL1 led to the accumulation of anthocyanin and a series of ABA-responsive gene transcripts in grape berries [30]. The expression of key enzymes in the anthocyanin biosynthesis pathway, including PAL, C4H, CHS, CHI, F3H, F3 H, DFR, and LDOX, was up-regulated by exogenous ABA in litchi [16] and strawberry [20].…”
Section: Discussionmentioning
confidence: 99%
“…Changes of polyphenol contents and gene expressions of vital enzymes involved in polyphenol biosynthesis under ABA and MLT treatments were presented in Figure 5. ABA has been widely recognized as a promotor to polyphenolic biosynthesis, and the increase in the expression of ABA receptor VIPYL1 led to the accumulation of anthocyanin and a series of ABA-responsive gene transcripts in grape berries [30]. The expression of key enzymes in the anthocyanin biosynthesis pathway, including PAL, C4H, CHS, CHI, F3H, F3 H, DFR, and LDOX, was up-regulated by exogenous ABA in litchi [16] and strawberry [20].…”
Section: Discussionmentioning
confidence: 99%
“…This challenge may explain, at least in part, the lack of functional studies using these grape infectious viral vectors. Other viral vectors like Tobacco rattle virus (TRV) and Apple latent spherical virus (ASLV) vectors can provoke VIGS in many plant species (Senthil-Kumar and Mysore, 2011) but not in grapevine, as recently confirmed by Gao et al (2018) who failed to silence VlPYL1 (pyrabactin resistance/PYL (PYR-like)) using the TRV-mediated silencing in "Kyoho" grapes. To the best of our knowledge, only one viral-derived vector was successfully used to perform functional studies in grapevine.…”
Section: Virus-derived Technologiesmentioning
confidence: 95%
“…This method is derived from the transient methodology successfully applied to tomato fruit (Orzaez et al, 2006) based on Agrobacterium cultures injection through the fruit stylar apex using a syringe with needle. Using this transient overexpression technique in the "Kyoho" grape fruit, Gao et al (2018) showed the involvement of the ABA Receptor VlPYL1 in the regulation of anthocyanin accumulation in grape berry skin. Similarly, Sun et al (2017) showed that VvVHP1;2 (vacuolar H + -PPase 1) overexpression promoted anthocyanin accumulation Lorenza Dalla Costa et al in berry skins.…”
Section: Agrobacterium-derived Technologiesmentioning
confidence: 99%
“…It was reported that SRPBCC domains have a deep hydrophobic ligand-binding pocket that can bind diverse ligands and spans all three kingdoms of life, but its function remains unclear. Moreover, SRPBCC-containing genes play a wide range of roles, including strawberry fruit ripening [22] , regulation of anthocyanin accumulation [23] , encoding type II secretion chaperones [24] , functioning in the stabilization of mRNA [25] , catalyzing the free radical reactions of polyunsaturated fatty acids [26] , and α-pyridone ring formation [27] . Hydroxylases that hydroxylate the C6 of pyridine, such as 3-succinoylpyridine dehydrogenase (SpmABC) [28] and picolinic acid dehydrogenase (PicA) [29] , include SRPBCC-containing components and are fused with [2Fe-2S] clusters, whereas most pyridine hydroxylases, such as NdhLSM and KdhLMS, have no SRPBCC domain (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%